Youth Unemployment in Post-Brexit UK: Evidence, Trends, and Policy Implications - Ugli, Karimov Islombek Bekpulat; Mulyani, Heni; Xajabayevna, Karlibayeva Raya (Tazkia Islamic University College, 2025)
This paper explores the dynamics of youth unemployment in the United Kingdom in the aftermath of Brexit, focusing on the structural, sectoral, and regional implications of labour market disruption between 2016 and 2023. Using a quantitative methodology based on secondary data from the Office for National Statistics (ONS), YouGov surveys, and the Oxford Migration Observatory, the study examines unemployment trends among individuals aged 16 to 24. While initial post-Brexit government responses—such as the Kickstart Scheme—resulted in short-term reductions in youth unemployment rates (from 13.5% in 2019 to 11.6% in 2023), the research identifies growing regional disparities and sector-specific job losses, particularly in manufacturing, services, and agriculture. Further, the study reveals a significant mismatch between educational outputs and market demands, which continues to hinder youth integration into the workforce. Special attention is paid to the policy environment that shaped these trends, including tightened immigration controls and skills-related policy gaps. Based on empirical data and a comparative review of earlier studies, this paper proposes practical policy recommendations aimed at improving youth employability, reskilling frameworks, and regional job creation strategies. The findings underscore the need for adaptive, data-driven policymaking to address the long-term effects of Brexit on youth employment and to prevent widening socio-economic inequalities across the UK.